The legal fatwa of the Indonesia council of ulama ( MUI ) on fajar Nusantara movement ( Gafatar ) ( perspectives of farid Esack and Jacques Derrida ) - M. Hudan Dardiri (Fak. Syariah dan Hukum UIN Sunan Kalijaga, 2019)
wt,1./ws.c.1